PENGARUH TINGKAT INTELEGENSI DAN MOTIVASI BELAJAR SISWA TERHADAP HASIL BELAJARFISIKA SISWA - Deo Valente; I Dewa Putu Nyeneng; Abdurrahman - (Jurnal Pembelajaran Fisika, 2012)
Learning is the most vital key term in every education effort, therefore without the real learning there will nothing about education. Individual achievement of the learning process called studying’s result. One of the internal factor that can influence someone’s studying result is intelegency and learning motivation. The research is to know : (1) The influence of the intelegensi against the learn physics the students , (2) The influence of motivation learn to the students learn physics the students , (3) The influence of the intelegensi and motivation learned to learn physics the students. This research was conducted in SMAN 13 Bandar Lampung that exerting one experimental class (X5) which 35 students as the sample. The studying’s result measured by the result of posttest evaluation, whereas the intelegency gained by taking from the research sample that use documentation technique. The data of learning motivation gain from the student’s learning motivation questionnaire. The data tested by SPSS 17.0 there are regression test, normality, homogenity and linearity. Based on the test result showed that : (1) There was influence of intelegency toward studying’s. (2) There was influence of motivation toward studying’s. (3) There was influence of intelegency and learning motivation toward studying’s.Keyword : studying’s result, intelegency and learning motivation.